AKTIVITAS LARVASIDA MINYAK ATSIRI PADA DAUN SIRIH (Piper betle Linn) TERHADAP LARVA NYAMUK Aedes aegypti - Oka Adi Parwata, I Made; Rahayu Santi, Sri; Sulaksana, I Made; Alit Widiarthini, Ida Ayu (Jurnal Kimia (Journal of Chemistry); Vol. 5, No. 1 Januari 2011)
Isolation and larvacide activity of essential oil from Piper betle Linn were studied. Approximately 13,5 mL of essential oil was obtained from 10,0 kg fresh leaves of Piper betle Linn. The oil is pale yellow with density of 0,7148 g/mL. Phytochemical test indicates that the content of the oil are terpenoid and phenol compounds with toxicity Aedes aegypty larvae 0f LC50= 309,03 ppm. The essential oil was toxic towards Aedes aegypty larvae because it contains phenol compounds, i.e. Eugenol, cavichol. GC-MS analysis reveals that there are 9 compound, i.e. 4-methyl(1-methylnethyl)-3-cyclohexen-1-ol, 1-methoxy-4(1-propenyl) benzene, 4-(2-propenyl)phenol/cavicol, 4-alylphenylacetate, Eugenol, Karyofilen, 3-alyl-6-methoxyphenylacetate, 4-alyl-1,2-diacetoxybenzene and decahydro-4a-methyl-1-methylene-7(1-methylethenyl) naphthalene. Based on the peaks intensity the oil was dominated by 4 compounds i.e. 4-allyl phenyl acetate, 2 methoxy-4-(2 prophenyl) phenol/eugenol, 3-allyl-6-methoxy phenyl acetate, 4-(2-prophenyl)-phenol / cavicol. These four compounds probably act as the active compounds to kill Aedes aegypty larvae, as they are acetate and phenol compounds.
Keywords: larvacide, essential oil, Piper betle Linn.leaf, Aedes aegypti larvae, LC50